PEMBELAJARAN DARING DALAM PEMBENTUKAN KARAKTER TANGGUNG JAWAB DAN DISIPLIN SISWA SEKOLAH DASAR - Yuni Hafidha; Erfantinni , (JP (Jurnal Pendidikan) : Teori dan Praktik, 2022)
This study aims to describe the implementation of online learning in the formation of the character of discipline and responsibility of elementary school students as well as the problems that arise. The method in this study is descriptive qualitative. This research was conducted at SD Negeri Kauman 2 Malang. The data collection techniques were; in-depth interviews, observations and documentation. Data analysis is carried out with steps consisting of data collection, data reduction, data presentation, and conclusion drawing. Based on this study, the result were (1) the planting of disciplinary character and responsibility is difficult to control by the school, due to distance restrictions; (2) there are a small percentage of parents who do not know their child's development because they are busy with work and cannot always guide their children when learning at home; (3) reviewed in terms of evaluation on character education, the absence of systematic evaluation using valid observations and instruments.